Stability-Indicating RP-HPLC Method for Simultaneous Estimation of Enrofloxacin and Its Degradation Products in Tablet Dosage Forms - V. Ashok Chakravarthy; B. B. V. Sailaja; Avvaru Praveen Kumar (Journal of Analytical Methods in Chemistry)
The present work was the development of a simple, efficient, and reproducible stability-indicating reverse-phase high performance liquid chromatographic (RP-HPLC) method for simultaneous determination enrofloxacin (EFX) and its degradation products including ethylenediamine impurity, desfluoro impurity, ciprofloxacin impurity, chloro impurity, fluoroquinolonic acid impurity, and decarboxylated impurity in tablet dosage forms. The separation of EFX and its degradation products in tablets was carried out on Kromasil C-18 (250×4.6 mm, 5 μm) column using 0.1% (v/v) TEA in 10 mM KH2PO4 (pH 2.5) buffer and methanol by linear gradient program. Flow rate was 1.0 mL min−1 with a column temperature of 35°C and detection wavelength was carried out at 278 nm and 254 nm. The forced degradation studies were performed on EFX tablets under acidic, basic, oxidation, thermal, humidity, and photolytic conditions. The degraded products were well resolved from the main active drug and also from known impurities within 65 minutes. The method was validated in terms of specificity, linearity, LOD, LOQ, accuracy, precision, and robustness as per ICH guidelines. The results obtained from the validation experiments prove that the developed method is a stability-indicating method and suitable for routine analysis.